Analisis Penggunaan Disfemisme pada Dialog Siswa Kelas IX dalam Pembelajaran di SMP Muhammadiyah 6 Surakarta - Fitriani, Fadillah; , Prof. Dr. Markhamah, M.Hum (2016)
This research regarding the value dysphemism sense, the cause of lack of compensation for language and context. This study aimed to describe the value of a sense phemism, causes lack of compensation for language and context of the dialog class IX students in learning in SMP Muhammadiyah 6 Surakarta. This study used a qualitative descriptive approach. The subjects were students of class IX SMP Muhammadiyah 6 Surakarta. Research data or snippets of speech corpus containing dysphemism spoken students. Data extracted from the primary data source. This research data collection techniques is the technique of recording/record, observation/observation, and interviews. Data analysis technique used in the study is equivalent pragmatic method. The results showed that: (1) the value dysphemism sense that arise include the value of a sense of creepy, horrific, frightening, disgusting, and bracing; (2) the cause of lack of benefit found among other critics speaking directly with harsh words, emotional or speakers, protective of opinions, deliberately accuse and discredit opponents said; and (3) the context of the emergence of dysphemism include physical and social context.